FAKTOR–FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NON-KEUANGAN - KURNIATI; ARIES JONATHAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this study was to obtain empirical evidence and to examine the effect of the independent variables on firm size, firm financial leverage, firm age, audit quality, independent commissioners, managerial ownership, institutional ownership and profitability on earnings management as the dependent variable in non-financial companies that listed on the Indonesia Stock Exchange (IDX). Financial statements can be used to assess the good or bad of a company so that companies often carry out earnings management to set off the financial statements. This study uses 151 non-financial companies listed on the Indonesia Stock Exchange (IDX) from year 2018 until year 2020. The method used in sampling is purposive sampling by determining five sample criteria and using multiple linear regression as a data analysis method. This study uses discretionary accruals which are calculated using the modified Jones model as a proxy for earnings management, natural logarithm to measure firm size variable, logarithm to measure firm age variable, audit quality variable and management ownership using dummy variable, and firm financial leverage variable, independent commissioner, institutional ownership and profitability are measured using a ratio scale. The results of this study indicate that firm size and profitability have an influence on earnings management, while firm age, firm financial leverage, audit quality, independent commissioners, managerial ownership and institutional ownership have no effect on earnings management.